Sustainability in an Emerging Market – In the context of the Top Management (2022)
The concept of CSR is still novel to Sri Lanka and firms in the country, and the adoption of the concept is in the initial phase. Scholars in developing countries are conducting studies based on CSR. This study aims to explore how and to what extent firms in emerging countries can conduct CSR activities; the types of benefits the firms can enjoy from CSR-driven activities; and the types of benefits that society can gain from CSR. This study provides insights into identifying existing CSR practices and analyze the benefits that they can generate. The study was conducted using 50 of the highest market capitalized firms listed on the Colombo Stock Exchange, Sri Lanka. The target group comprised 70 board of directors of the selected firms. A structured questionnaire was used for collecting data. The board of directors who responded believed that the most vital criteria in the CSR pyramid are economic responsibility. This response indicates that firms need to prioritise generating profits and then use their earnings for the wellbeing of society.